THE DISCUSSION ON THE NATION-STATE AND CITIZENSHIP EDUCATION IN THE PROCESS OF GLOBALIZATION - Ufuk ŞİMŞEK (Fırat University, 2019)
The revival of ethnic structures, massive migration rates between the countries and nation-states by the process globalization quickly produces pluralistic values in today's World. In this situation causes both new common values and contradictions occurred in contemporary societies. Humanity has been faced with so far unprecedented the inevitability of living together. 19 and 20 th centuries, states with nationalist ideologies used education the process of nation-building. The states with used especially social studies education and citizenship education for create identity that wished. Today, we witness this process is exposed to erosion. Usually, efforts of creating national identity that is to be built in citizenship education programs undergo inevitably change and transformation. How can nation-states respond this process with maintaining existing grounds? Which common values will be our teaching aims process of globalization? May liberal values be the common values of all mankind? These questions will be issues on the agenda in the coming years. This study aims how to show some ideas in citizenship education in coming years due to global and pluralistic structures pressures that controlled by state and static social structures. No matter how it is performed, citizenship education is inevitable activity for humanity. However, as in any fields, important changes and transformations are realized in this subject. A process of existing universal value norms (Human Rights Act) signed by almost all countries and societies, it doesn’t seem possible for static societies to transmit their identity to next generations. The existence of mass media, international organizations, immigration, global economy and law doesn’t recognize any border and spreading the whole world rapidly. The old political and social reflexes show resistance to this change. However, it is impossible to remain without any reaction to this change. Nation-states have adopted some new insights in citizenship education. The democratic and liberal values as general principles of citizenship education can widely accepted but not shared universally. Liberal values are challenged by secular ideologies such as Marxism, existentialism, radical feminism, postmodernism and religions such as the evangelist Christian, Catholic and Islamic religions.